Travessias de Cecília: a caminho da educação matemática no CEEJA Padre Moretti - Rondônia - Cordeiro, Edna Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Initially, this research intended only realize the scenario of Mathematics Education in the Centro Estadual de Educação de Jovens e Adultos (CEEJA) Padre Moretti, the historical path from 1977 to 2012, but the go thru the perspective of the New Cultural History as thought by Chartier (1990), the survey was expanded from data obtained on the performance of that center, the story of Rondônia and the family of Cecilia character of this text. Consequently, were also discussed formative processes of character and other teachers in Rondônia. The data emerging from the creation of documents such as laws, resolutions and ordinances (legal framework) referencing EJA courses in Rondônia; designs found in the archives of CEEJA; located in old newspapers library Francisco Meirelles, and memories of Cecilia and ten respondents (graduates and professors). Interpretations we had from the collected data gave rise to the polyphonic text and dialogical perspective of Bakhtin (2011). The concept of culture, from Geertz (2008) enabled the construction of history, that is, Cecilia crossings in search of an understanding about the plot of this text that moves between difficulties and opportunities of characters text and Education in the state of Rondônia. With regard to history of Rondônia, was perceived diversity of opportunities work up and the population of financial improvements, however were always present many difficulties, such as lack of infrastructure, education and health, and political performances uncommitted to the general population. In the history of Education Youth and Adults (EJA) in Rondônia and CEEJA moments were identified oscillations between extending the decline in attendance and performances and the number of students of the institution. When analyzing the data on Mathematics, the most frequently observed difficulties in the learning process were: lack of prior knowledge of students to accompany a curriculum geared toward...

De início, esta investigação pretendia apenas perceber o cenário da Educação Matemática no Centro Estadual de Educação de Jovens e Adultos (CEEJA) Padre Moretti, no percurso histórico de 1977 a 2012, mas, ao percorrer caminhos na perspectiva da Nova História Cultural como a pensada por Chartier (1990), a pesquisa se ampliou a partir de dados obtidos sobre a atuação daquele Centro, da história de Rondônia e da família de Cecília, personagem deste texto. Por consequência, também foram discutidos os processos formativos da personagem e de outros professores em Rondônia. Os dados emergiram da constituição de documentos, tais como: leis, resoluções e portarias (marcos legais) que referenciam os cursos de EJA em Rondônia; projetos encontrados nos arquivos do CEEJA; jornais antigos localizados na biblioteca Francisco Meirelles, e as memórias de Cecília e de dez entrevistados (egressos e professores da instituição). As interpretações realizadas a partir dos dados coletados deram origem ao texto polifônico e dialógico, na perspectiva de Bakhtin (2011). A concepção de cultura, a partir de Geertz (2008), possibilitou a construção da história, isto é, as travessias de Cecília, em busca de uma compreensão sobre o enredo deste texto que se move entre dificuldades e oportunidades das personagens, bem como da Educação no estado de Rondônia. No que se refere à história de Rondônia, foi percebida a diversidade de oportunidades de trabalho e até de melhorias financeiras de parte da população, entretanto muitas dificuldades sempre estiveram presentes, como a falta de infraestrutura de educação e saúde, além de atuações políticas descompromissadas com a população em geral. Na história da Educação de Jovens e Adultos (EJA) em Rondônia e no CEEJA foram identificados momentos de oscilações entre a ampliação do atendimento e declínio nas atuações e no número de alunos da Instituição. Ao analisar os...
Keywords: Mathematics - Study and teaching; Matemática - Estudo e ensino; Educação de adultos; Matemática - História; Professores - Formação; Pratica de ensino; Rondonia - História